Follow-up: maternal perception on child monitoring - Mirna Albuquerque Frota; Ivna Silva Andrade; Yohanna Andrade Moreira Monteiro; Conceição Maria de Albuquerque; Ana Paula Soares Gondim (Universidade Estadual de Maringá, 2014)
Maternal perception on follow-up monitoring towards the improvement of  children's care is investigated. Current descriptive qualitative study was performed at the outpatient clinic of a secondary care hospital in Fortaleza, Ceará State, Brazil, from July to September 2010. Half-structured interviews were undertaken with 16 mothers who accompanied their children in the follow-up. Minayo thematic analysis enabled data categorization in Child Development, Continuing Care, Importance of Follow-up. The monitoring of children discharged from intensive care units is relevant for the prevention of injuries in neuropsychomotor development. The exchange of information and guidance received during follow-up visits provided support to mothers devoted to child care and promoted trust and confidence for care continuation. Health professionals have a role beyond the care itself, or rather, the provision of educational support through the interactive process, including family-provided assistance which becomes part of the method of caring.